The measurement and dimensionality of e-learning blog satisfaction. Issue 5 (30th September 2014) - Wang, Yi-Shun; Li, Ci-Rong; Lin, Hsin-Hui; Shih, Ying-Wei
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop and validate a multi-dimensional instrument to measure e-learning blog satisfaction (ELBS). Design/methodology/approach – This study introduces and defines the construct of ELBS, provides an empirical validation of the construct and its underlying dimensionality, develops a generic ELBS instrument with desirable psychometric properties, and investigates the instrument's theoretical and practical applications. Findings – After analyzing data from a calibration sample (n=238) and a validation sample (n=226), this study proposes a five-factor, 20-item ELBS instrument. Practical implications – This empirically validated instrument will be useful to researchers in terms of developing and testing blog-based learning theories, as well as to educators in terms of understanding students' ELBS and promoting the use of blog-based learning systems. Originality/value – This study is a pioneering effort to develop and validate a multi-dimensional instrument to measure ELBS.